Dans le secret de la juridiction domestique. Le châtiment des femmes dans la Rome antique - Julie Meyer (Droit et Cultures, 2023)
This study examines the fate of female criminals in ancient Rome. Most of the time, even when a criminal woman had been openly condemned, punishment was often administrated by the private sphere, for utmost discretion. Secrecy therefore was a prime goal when it came to crimes such as adultery or consumption of wine: the problem was resolved within the household, by the husband or possibly by members of the family. Understanding the reasons for such secrecy surrounding the punishment of criminal women will help to see if sometimes, in certain cases, this discretion was discarded in favor of a public sentence and if therefore the secrecy surrounding the fate of the criminal woman could sometimes be broken.